2018
DOI: 10.3390/ma11040649
|View full text |Cite
|
Sign up to set email alerts
|

On the Phase Separation in n-Type Thermoelectric Half-Heusler Materials

Abstract: Half-Heusler compounds have been in focus as potential materials for thermoelectric energy conversion in the mid-temperature range, e.g., as in automotive or industrial waste heat recovery, for more than ten years now. Because of their mechanical and thermal stability, these compounds are advantageous for common thermoelectric materials such as Bi2Te3, SiGe, clathrates or filled skutterudites. A further advantage lies in the tunability of Heusler compounds, allowing one to avoid expensive and toxic elements. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Recent work using unfolded supercell calculations has shown that new bands can emerge in substituted HH compositions (e.g. in vacancy systems, 170 for interstitials 58 and complex compositions 233 ) and this is another possible route for performance improvements. This is an area where theory could lead experiments by identifying new compositions with promising electronic bandstructures.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Recent work using unfolded supercell calculations has shown that new bands can emerge in substituted HH compositions (e.g. in vacancy systems, 170 for interstitials 58 and complex compositions 233 ) and this is another possible route for performance improvements. This is an area where theory could lead experiments by identifying new compositions with promising electronic bandstructures.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…In the past few decades, the exploration of renewable/alternative energy technologies has been accelerated to minimize the dependency of human activities on fossil fuels, which are deeply responsible for global warming, air pollution, and climate changes, etc. More than two-third part of the energy produced in our economy is wasted in the form of heat . If even a small part of this waste heat can be utilized, then it would lead to reducing the consumption of non-renewable sources of energy and may be helpful in limiting climate changes to an extent.…”
Section: Introductionmentioning
confidence: 99%
“…More than two-third part of the energy produced in our economy is wasted in the form of heat. 1 If even a small part of this waste heat can be utilized, then it would lead to reducing the consumption of nonrenewable sources of energy and may be helpful in limiting climate changes to an extent. Thermoelectrics (TEs) offer a prospective means for energy harvesting or waste heat recovery.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning that first-principles calculations have provided the guideline for developing new promising HH-based TE materials. Up to now, experimental investigations on HH compounds have mainly focused on n-type M NiSn [ 30 , 31 , 32 , 33 , 34 ]. There is only a very small fraction of studies on other HH systems [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%